Spatial Analysis of Drug-Prone Areas in Jakarta to Enhance City Resilience - Agustina, Saur Martha; Chotib, Chotib; Sinaga, Hariati (Security Intelligence Terrorism Journal (SITJ), 2024)
Resilience has emerged as a central theme in urban planning, offering a strategic framework to manage city development while promoting sustainability. This is particularly important for Jakarta as it ranks among the world's significant cities highly susceptible to diverse challenges and disruptions. This includes vulnerability to drug crime cases. As one of the efforts to overcome vulnerability, it is necessary to analyze drug-prone areas in Jakarta based on urban villages. The purpose of this study is to analyze the spatial distribution of drug-prone areas in Jakarta using Geographic Information Systems (GIS) and to analyze the role of factors determining the level of drug-prone areas in Jakarta province by applying an ordinal logit regression model. The results of this research show that almost all independent variables have no significant impact on the level of drug-prone areas. The result shows that the presence of foreigners has a significant impact on the level drug prone areas. The research findings recommend tighter monitoring of the presence of foreigners.